Real-time analysis of the biomolecular interaction between gelsolin and Aβ1-42 monomer and its implication for Alzheimer's disease - Ma, Limin; Meng, Tian; Wang, Yu; Xue, Yu; Zheng, Yuxin; Chen, Jinghuang; Xu, Dongming; Sun, Jian; Yang, Fan; Huang, Jianshe; Yang, Xiurong (Talanta (Oxford), 2025)
Biomolecular interaction acts a pivotal part in understanding the mechanisms underlying the development of Alzheimer's disease (AD). Herein, we built a biosensing platform to explore the interaction between gelsolin (GSN) and different β-amyloid protein 1-42 (Aβ1-42) species, including Aβ1-42 monomer (m-Aβ), Aβ1-42 oligomers with both low and high levels of aggregation (LLo-Aβ and HLo-Aβ) via dual polarization interferometry (DPI). Real-time molecular interaction process and kinetic analysis showed that m-Aβ had the strongest affinity and specificity with GSN compared with LLo-Aβ and HLo-Aβ. The impact of GSN on inhibiting aggregation of Aβ1-42 and solubilizing Aβ1-42 aggregates was evaluated by circular dichroism (CD) spectroscopy. The maintenance of random coil structure of m-Aβ and the reversal of β-sheet structure in HLo-Aβ were observed, demonstrating the beneficial effects of GSN on preventing Aβ from aggregation. In addition, the structure of m-Aβ/GSN complex was analyzed in detail by molecular dynamics (MD) simulation and molecular docking. The specific binding sites and crucial intermolecular forces were identified, which are believed to stabilize m-Aβ in its soluble state and to inhibit the fibrilization of Aβ1-42. Combined theoretical simulations and experiment results, we speculate that the success of GSN sequestration mechanism and the balance of GSN levels in cerebrospinal fluid and plasma of AD subjects may contribute to a delay in AD progression. This research not only unveils the molecular basis of the interaction between GSN and Aβ1-42, but also provides clues to understanding the crucial functions of GSN in AD and drives the development of AD drugs and therapeutic approaches. Gelsolin and Aβ1-42 with different levels of aggregation are key proteins related to the molecular mechanism of Alzheimer's disease (AD). We studied the real-time binding behaviors between them via dual polarization interferometry (DPI). Their kinetic processes and the key binding sites were further displayed, revealing abundant information about AD from novel viewpoints and covering issues of concern in multiple fields. [Display omitted] •A real-time biosensing platform was built via dual polarization interferometry (DPI) to explore the binding behavior and kinetic aspect between gelsolin (GSN) and different Aβ1-42 species.•The affinity of Aβ1-42 monomer and GSN was considerably greater than Aβ1-42 oligomers with both low and high levels of aggregation.•GSN could reduce amyloid load by inhibiting m-Aβ aggregation and solubilizing Aβ1-42 aggregates.•The random coil structure, hydrogen bond and hydrophobic region jointly contribute the dominant combination of GSN and Aβ1-42 monomer.